2008
DOI: 10.1124/mol.108.048892
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pharmacophores for the Selective Activation of Nicotinic α7-Type Acetylcholine Receptors

Abstract: The activation of heteromeric and homomeric nicotinic acetylcholine receptors was studied in Xenopus laevis oocytes to identify key structures of putative agonist molecules associated with the selective activation of homomeric ␣7 receptors. We observed that selectivity between ␣7 and ␣4␤2 was more readily obtained than selectivity between ␣7 and ␣3␤4. Based on structural comparisons of previously characterized selective and nonselective agonists, we hypothesize at least three chemical motifs exist that, when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 49 publications
2
80
0
Order By: Relevance
“…It was proposed that the large hydrophobic groups present on ␣7-selective agonists such as the BA compounds are accommodated within a comparably large hydrophobic pocket in the ␣7 agonist binding site (Horenstein et al, 2008). This would be consistent with the hypothesis that these agonists may remain bound to the receptor even after being washed out of the bath.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…It was proposed that the large hydrophobic groups present on ␣7-selective agonists such as the BA compounds are accommodated within a comparably large hydrophobic pocket in the ␣7 agonist binding site (Horenstein et al, 2008). This would be consistent with the hypothesis that these agonists may remain bound to the receptor even after being washed out of the bath.…”
Section: Resultssupporting
confidence: 70%
“…Many experimental agents have been identified that selectively activate ␣7 nAChR (Horenstein et al, 2008). The structural diversity of these agents is matched by a diversity in their functional properties, for example, in regard to whether they act as antagonists of other nAChR subtypes and/or 5-hydroxytryptamine 3 (5HT 3 ) receptors.…”
mentioning
confidence: 99%
“…Both academic and industrial laboratories have discovered numerous agonists with selectivity for ␣7 receptors (Horenstein et al, 2008), and in recent years an alternative therapeutic approach based on allosteric modulation has gained momentum because of the discovery of many structurally diverse positive allosteric modulators (PAMs) that are selective for ␣7 receptors (Williams et al, 2011c). To date, the ␣7 PAMs are classified into one of two categories based on their properties of modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The most potent and selective compound, triazole 22 q , features a positively charged N-methylammonium tropane and aromatic methyleneoxynaphthylenethanone. The other products formed revealed pharmacophore models for leads that were consistent with studies on ␣7 nAChRs (Horenstein et al, 2008), which demonstrated the recognition capacity of the template to select preferred binding partners. Structural Insights into ␣7 nAChR Selectivity from AChBP Data.…”
Section: Discussionmentioning
confidence: 50%